Heterosis: current advances in the search for molecular mechanisms - M. N. Shapturenko; L. V. Khotyleva (Вавиловский журнал генетики и селекции)
Heterosis as the increased performance of hybrid progeny compared to their inbred parents is one of the most intriguing phenomena in genetics. The first attempts to find out about underlying mechanisms were based on theoretical models, which were useful, but could not characterize this unique phenomenon as a whole. With the advent of molecular markers great efforts were made to identify genomic regions causing heterotic response and clarify prospects of using information about molecular divergence of parental forms as a criterion for the prediction of F1 performance. Despite some achievements, the effec-tiveness of both molecular divergence and prospective heterotic QTL for practical goals was limited, confirming that genetic heterogeneity is necessary, but not sufficient to produce perfect phenotype. Current methodological tools of functional genomics and related disciplines have provided new opportunities for searching for mechanisms of heterosis at different levels in the context of relative importance of dominance, overdominance and epistasis. To date, differences in genome organization, gene expression and epigenetic status have been found between hybrids and their parents. At the genomic level, some QTLs associated with heterosis were identified and the impact of DNA divergence on F1 performance was evaluated. At the level of transcriptome, it was shown that heterosis in hybrids occurs along with changes in gene expression regulation under the influence of circadian clock genes. Several studies have been conducted to clarify the role of epigenetic DNA modification and genomic imprinting in the manifestation of heterosis. Taken together, data indicates that heterosis cannot been explained by a single common mechanism, because this complex phenomenon involves many components, a cumulative effect of which leads to the formation of an outstanding phenotype.